REALIZING INDEPENDENT VILLAGES THROUGH VILLAGE DEVELOPMENT PLANNING - Mersa, Sudarman; Rakhmadani, Syeni; Wardhana, Yuditya; Gusnita, Ari (Pasundan International of Community Services Journal (PICS-J), 2023)
The paradigm change in the system of government of the Republic of Indonesia which is carried out in a decentralized manner makes the village government have the authority to regulate and manage its own government independently. In order to create an independent village, one thing that needs to be considered in village development is the planning stage. However, there are still many Village Development Plans that are made by villages immaturely, one of which is in Siraman Village, Pekalongan District, East Lampung Regency. This service activity aims to provide knowledge about realizing an independent village through village development planning through the solicitation method. The results of this activity indicated an increase in the knowledge of the participants by 41%